Pressure profiles of High Energy Beam Transport vacuum system for the FAIR project. (December 2015) - Suherman, P.M.; Kraemer, A.; Urban, L.; Bellachioma, M.C.; Cavaco, J.
Abstract: The pressure profile calculations of some beam lines from the High Energy Beam Transport (HEBT) vacuum system for the FAIR (Facility for Antiproton and Ion Research) accelerator facility are presented in this report. The calculations used both a simple analytical model and a Monte-Carlo method for a steady-state condition. The calculation results show that the pressure profiles for these beam lines are conductance limited. A simple experimental setup representing a small part of the HEBT section was also conducted. Highlights: Pressure profile calculations of High Energy Beam Transport (HEBT) vacuum system. Comparison of two simulation methods for pressure profiles of High Energy Beam Transport (HEBT) vacuum system. The pressure profile calculations for different pumping speed shows that the HEBT vacuum chambers are conductance limited.